Hadis dan Sunnah sebagai Landasan Tradisi dalam Islam: Analisis Historis Terminologis - Emawati Emawati (Ulumuna, 2011)
The second source of Islamic law is the sunnah or hadîts. This is not something new and disputed again by all Muslims, but the issue is whether the two terms have the same sense? Western as well as Islamic scholars question the definition of both terms and its use because it has implications for the nature of authority and authenticity of both as a foundation in Islamic tradition. It will be revealed in this paper in historical perspective the development of definition and use of the terms, hadîts and sunnah, since the early generation, time of the Prophet Muhammad, until now. A variety of referral sources originating from Western and Islamic scholars are traced and studied in order to find the meeting point of difference of views developed on these two terms.